Assessment of Drivers’ Perceptions of Connected Vehicle–Human Machine Interface for Driving Under Adverse Weather Conditions: Preliminary Findings From Wyoming - Ahmed, Mohamed M.; Yang, Guangchuan; Gaweesh, Sherif (Frontiers in Psychology, 2020)
Connected Vehicle (CV) technology aims to improve drivers’ situational awareness through audible and visual warnings displayed on a Human-Machine Interface (HMI), thus reducing crashes caused by human error. This paper developed a driving simulator testbed to assess the readability and usefulness of the Wyoming CV applications. A total number of 26 professional drivers were recruited to participate in a driving simulator study. Prior to driving the simulator, the participants were trained on both the concept of CV technology and the developed CV applications as well as the operation of the driving simulator. Three driving simulation scenarios were designed. For each scenario, participants drove two times; one with the HMI turned-on and another one with the HMI turned-off. After driving the simulator, a comprehensive revealed-preference survey was employed to collect the participants’ perceptions of CV technology and Wyoming CV applications. Results showed that the Wyoming CV applications were most favored under poor-visibility driving conditions. Among the Wyoming CV applications, Forward Collision Warning (FCW) and Re-Routing applications were experienced as the most useful. Approximately 89 percent of the participants stated that the Wyoming CV applications provided them with improved road condition information and increased their experienced safety while driving; 65 percent of the participants stated the CV applications and the HMI did not introduce distraction from the primary task of driving. Finally, this paper concluded that the design of CV HMI needs to balance a tradeoff between the readability of the warnings and drivers’ capability to safely recognize and timely respond to the received warnings.